Toward a fully wireless endovascular neural interface: Evaluating power transfer efficacy - Yi-De Tai; Joel Villalobos; Nima Wickramasinghe; Bryce Widdicombe; Ranjith R. Unnithan; David B. Grayden; Sam E. John (PLoS ONE, 2026)
Background Endovascular neural interfaces (ENIs) offer a minimally invasive approach for neural stimulation and recording without the need for open brain surgery. However, current generation devices have long transvascular wires from the implant site to the chest. Eliminating these wires will unlock clinical usability, including lowering infection risk from transvascular wires, reducing the risk of thrombosis from altered hemodynamics, and improving mechanical reliability. However, removing these transvascular wires would require efficient power transfer across the skull and tissue while meeting specific absorption rate (SAR) limits, which is a significant challenge in the field. Objective This work designed and evaluated endovascular receiver (Rx) and transmitter (Tx) coils within endovascular geometric and biological constraints to maximize wireless power transfer. Methods This study evaluated the optimal operating frequencies, quantified coupling, coil quality factors, power transfer efficiency, and SAR using computational modeling, benchtop, and in-vivo testing. The study also assessed the tolerance to coil misalignment and load mismatch. We evaluated each case with and without ferrites with measurements in air, sheep tissue, and in vivo in sheep. Results The results showed that inductive power transfer delivered power to endovascular geometry devices at clinically relevant depths. The maximum power transfer efficiency (PTE) reached 11% at 15 mm and 2% at 30 mm, with up to 72 mW delivered at 30 mm under SAR safety limits. The rectangular planar coil pair performed best at ≤15 mm, whereas the ferrite-core flux-pipe Tx with a helical Rx outperformed beyond ~20 mm and was more tolerant to misalignment. Conclusion This study demonstrated the feasibility of wirelessly powering multichannel ENIs using coils that can be placed inside a blood vessel and powered inductively. Making an endovascular neural interface fully wireless has the potential to transform the technology by improving both safety and reliability.